Enhancing Religious Moderation through Islamic, Christian, and Buddhist Religious Subject in the Context of Character Education - Dwi Sulistyowati; Nur Ulayatun Nida; Purnomo; Muhammad Faiz Naufal (Indonesian Values and Character Education Journal, 2025)
The increasing symptoms of intolerance and exclusivism in educational settings have the potential to weaken social cohesion and hinder the formation of students’ national character. This condition indicates the need for pedagogical strategies that systematically instill the values of tolerance, justice, and respect for diversity within the learning process. This study aims to analyze and explore the strengthening of religious moderation through Islamic, Christian, and Buddhist religious instruction in heterogeneous school contexts. The research employed a qualitative approach with a phenomenological design involving religious education teachers and students as participants. Data were collected through classroom observations, in-depth interviews, and document analysis using structured guidelines, and were analyzed thematically through data reduction, data display, and conclusion drawing with triangulation to ensure validity. The findings reveal that strengthening religious moderation is implemented through the integration of national values, participatory humanistic approaches, the provision of safe spaces for student expression, and objective character-based assessment, which contribute to the development of tolerant, inclusive, and fair attitudes in interfaith interactions. In conclusion, moderation based religious education represents an effective learning paradigm for building national character and strengthening social cohesion among students. The implication of this study underscores the importance of systematically and sustainably integrating religious moderation values into curriculum design and pedagogical practices within multicultural educational environments.